Business Reputation and Labor Efficiency, Productivity, and Cost - Stuebs, Marty (Journal of business ethics, 2010)
Assumed benefits from improved reputation are often used as motives to drive corporate social responsibility (CSR) initiatives. Are improved cost efficiencies among these reputation benefits? Cost efficiencies and cost management have become more relevant as revenue streams dry up in these tough economic times. Can a good reputation aid these efforts to develop cost efficiencies specifically when managing labor costs? Prior research hypothesizes that good reputation can create labor productivity and efficiency benefits. The purpose of this study is to empirically investigate reputation’s relationship with labor efficiency, labor productivity, and labor cost. Using a sample of highly reputable firms from Fortune’s America’s Most Admired Companies list and a corresponding matched sample of firms, we find that reputation is associated with improved labor efficiency and labor productivity. However, we do not find a significant association between reputation and reduced labor costs. Our study contributes to current research hypothesizing and finding efficiency benefits associated with good reputation. Documenting these potential reputation benefits has important implications for CSR activities and initiatives. It supports recent work that incorporates reputation into a more developed model of the relationship between CSR and performance (Vilanova et al.: 2009, Journal of Business Ethics 87, 57–69). This work is useful to businesses and supports strategies focused on “doing well by doing good” and maintaining healthy reputations.